Madame Bovary, c’est moi! : - Bernard, Andre (W.W. Norton, 2004)
The struggles and inspirations that gave birth to our great writers' most memorable creations. A delightful compendium of wit and information, this book takes us on a casual stroll through literary history as the world's most successful writers sought just the right name, or just the right tone, or just the right prop, for the hero or heroine of their works.